Profiling of volatile compounds in beef, rat, and wild boar meat using SPME-GC/ MS - Lia Amalia; Kusnandar, Feri; Nancy Dewi Yuliana; Purwantiningsih Sugita (Penerbit Universiti Kebangsaan Malaysia, 2022)
The high beef price triggers adulteration of beef and other non-halal animal meat, such as wild boar and rats. An appropriate and effective analytical method is needed to differentiate halal and non-halal animal meat. The SPME/ GC-MS method could authenticate meat based on specific volatile compounds in each meat. The objective of this study was to characterize volatile compounds and determine the volatile marker in raw beef, rat, wild boar meat, and their mixtures using SPME/GC-MS. The chemometrics of principal component analysis (PCA) and orthogonal projection to latent structure-discriminant analysis (OPLS-DA) classified raw beef, rat, wild boar, and their mixture. Correlation coefficients and VIP values were used to determine the volatile marker compounds for each meat in the OPLS-DA classes. The OPLS-DA results that the most robust marker in the beef class was dimethylfulvene, benzyl alcohol in the rat class, and 1,3,5-cycloheptatriene in the wild boar class. Furthermore, the most robust marker in the mixture of beef and rat class was benzaldehyde, 3-ethyl-, while 2,6-dimethyldecane was dominant in the mixture of beef and wild boar class. However, further study using larger number of samples which include commercial meat is required to confirm these results.